1966
DOI: 10.1002/1097-0142(196604)19:4<489::aid-cncr2820190406>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological investigation of cancer of the endometrium

Abstract: One hundred‐twelve endometrial cancer patients and 200 comparison patients were interviewed in New York hospitals. Additionally, the hospital records of more than 900 patients with endometrial cancer were reviewed. The most important factor found related to cancer of the endometrium is obesity. Tallness, in addition to obesity, enhances the risk of endometrial cancer distinctly. Other differences between the cancer patients and the comparison subjects, including late menopause, heavy menstrual bleeding and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
44
0
4

Year Published

1968
1968
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(59 citation statements)
references
References 63 publications
11
44
0
4
Order By: Relevance
“…In the absence of a previous diagnosis of breast cancer the most consistently reported risk factors for endometrial cancer are nulliparity, late age at menopause, obesity, and oestrogens for menopausal symptoms (Elwood et al, 1977;Ewertz, 1981;Kelsey et al, 1982;La Vecchia et al, 1982;MacMahon, 1974;Salmi, 1979;Wynder et al, 1966). Our results closely agree with those studies.…”
Section: Discussionsupporting
confidence: 90%
“…In the absence of a previous diagnosis of breast cancer the most consistently reported risk factors for endometrial cancer are nulliparity, late age at menopause, obesity, and oestrogens for menopausal symptoms (Elwood et al, 1977;Ewertz, 1981;Kelsey et al, 1982;La Vecchia et al, 1982;MacMahon, 1974;Salmi, 1979;Wynder et al, 1966). Our results closely agree with those studies.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the results of studies of older mainly postmenopausal women (Damon, 1960;Wynder et al, 1966;Elwood et al, 1977;Kelsey et al, 1982;La Vecchia et al, 1982). Incomplete pregnancies also appear to be protective.…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that obesity is a major risk factor for endometrial cancer in post-menopausal women (Damon, 1960;Wynder et al, 1966;Elwood et al, 1977;Kelsey et al, 1982;La Vecchia et al, 1982), and case reports have suggested that young endometrial cancer cases tend to be very obese (Sommers et al, 1949;Dockerty et al, 1951;Peterson, 1968). In our population 50% (55/110) of the cases weighed 2150lbs, and the associated attributable risk percent (ARP) is 38%, i.e.…”
Section: Discussionmentioning
confidence: 66%
“…23 SIRT1 was reported to be involved in the longevity induced by caloric restriction, 10 and its function in DNA repair and control of the cell cycle 24 was found to be similar to that of a tumor suppressor gene. Therefore, we first hypothesized that SIRT1 may be downregulated in the normal or cancerous tissues of women with a high BMI.…”
Section: Discussionmentioning
confidence: 99%